Crumbs, Moesin and Yurt regulate junctional stability and dynamics for a proper morphogenesis of the Drosophila pupal wing epithelium. Issue 1 (December 2017) - Salis, Pauline; Payre, Francois; Valenti, Philippe; Bazellieres, Elsa; Le Bivic, André; Mottola, Giovanna
Abstract The Crumbs (Crb) complex is a key epithelial determinant. To understand its role in morphogenesis, we examined its function in theDrosophila pupal wing, an epithelium undergoing hexagonal packing and formation of planar-oriented hairs. Crb distribution is dynamic, being stabilized to the subapical region just before hair formation. Lack ofcrb orstardust, but notDPatj, affects hexagonal packing and delays hair formation, without impairing epithelial polarities but with increased fluctuations in cell junctions and perimeter length, fragmentation of adherens junctions and the actomyosin cytoskeleton. Crb interacts with Moesin and Yurt, FERM proteins regulating the actomyosin network. We found that Moesin and Yurt distribution at the subapical region depends on Crb. In contrast to previous reports, yurt, but notmoesin, mutants phenocopycrb junctional defects. Moreover, while unaffected incrb mutants, cell perimeter increases inyurt mutant cells and decreases in the absence ofmoesin function. Our data suggest that Crb coordinates proper hexagonal packing and hair formation, by modulating junction integrity via Yurt and stabilizing cell perimeter via both Yurt and Moesin. TheDrosophila pupal wing thus appears as a useful system to investigate the functional diversification of the Crb complex during morphogenesis, independently of its role in polarity.